(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Sickle cell disease (SCD) is among the most common single-gene disorders globally, classified as an autosomal recessive condition causing chronic anemia, painful vaso-occlusive crises, progressive multi-organ damage, and reduced lifespan. Cardiopulmonary complications are leading causes of morbidity and mortality. Objective: To evaluate cardiopulmonary risk using serum NT-proBNP levels and transthoracic echocardiography in children with sickle cell disease at a tertiary care center in Jharkhand. Methods: A hospital-based cross-sectional study was conducted on 73 children (aged 5–18 years) with confirmed SCD. Detailed clinical, laboratory, and standardized echocardiographic evaluations were performed, alongside quantitative measurements of serum NT-proBNP levels. Results: Elevated NT-proBNP levels (>100 pg/mL) were found in 63% of participants, with a mean level of 142.6 ± 98.4 pg/mL. Echocardiography revealed left ventricular hypertrophy (LVH) in 35.6%, diastolic dysfunction in 42.5%, and pulmonary hypertension (elevated tricuspid regurgitant velocity, TRV >= 2.5 m/s) in 38.4% of patients. Left ventricular systolic function remained largely preserved (mean EF 64.2% ± 5.8%). NT-proBNP levels correlated significantly with lower hemoglobin (r = -0.486, p < 0.001), reticulocytosis (r = +0.396, p = 0.001), elevated TRV (r = +0.642, p < 0.001), and high E/e’ ratio (r = +0.568, p < 0.001). Multivariate analysis identified TRV >= 2.5 m/s (OR 5.26), hemoglobin < 7 g/dL (OR 3.84), and diastolic dysfunction (OR 2.98) as independent predictors of elevated NT-proBNP levels. Conclusion: Subclinical cardiopulmonary involvement is highly prevalent in pediatric sickle cell disease in Jharkhand. Routine screening with echocardiography and NT-proBNP can aid in early risk stratification and target timely therapeutic interventions.